Efeitos de lâminas e frequências de irrigação e de tipos e volumes de substrato na aclimatização de mudas micropropagadas de abacaxizeira ornamental - Bomfim, Guilherme Vieira do (2006)
The ornamental pineapple is a rustic and exotic spe cies that it produces "flowers" of great beauty, appreciated by consumers of the whole world . In the present time, due to the high demand of the consumer market, the culture is being produced in commercial scale through the micropropagation, a tissue culture technique th at presents five important stages. One of them, the acclimatization, is a very critic phase b ecause it answers for the high death rates and low growth rates of the plants. This happens becaus e the little information about the culture management in this phase is based on the empiricism most of the time. Therefore, the needs of acclimatized plants are not meet, what takes to considerable losses and/or acquisition of seedlings of variable quality. To minimize this pro blem and to fill out the existent gap with technical and scientific information about the appr opriate culture management, the objective of this work was to evaluate the effects of differe nt irrigation levels and frequencies and different types and volumes of substrate in the acc limatization of micropropagated seedlings of ornamental pineapple (Ananas comosusvar.erectifolius ). The research was carried out in a greenhouse of the Embrapa Tropical Agroindustry, located at Fortaleza-CE (3º44' S and 38º33' W) and it consisted of four experiments. Four irrigation levels were analyzed in the first experiment: 1, 2, 3 and 4 mm. The plants, cultivated in the green coir dust substrate with wormcompost (3:1) in 180 cm 3 plastic containers, were irrigated twice a day. Four watering frequencies were studied in the second experiment: 1, 2, 3 and 4 irrigations by the day. The plants were cultivated in 180 cm 3 plastic containers that contained green coir dust substrate with wormcompost (3:1) and they were irrigated with a 3 mm water level. Four different combinations of substrate were tested in the third experiment 3:1: dry coir dust with Vitasolo ®; dry coir dust with wormcompost; green coir dust substrate with Vitasolo® and green coir dust substrate with wormcompost. The plants, cultivated in the different substrates in 180 cm3 plastic containers, were irrigated with a 3 mm water level twice a day. Four plastic container types were evaluated in the fourth experi ment: 300 cm 3 plastic container; 180 cm 3 plastic container; tray of 40 cm 3·cell −1 and tray of 30 cm 3 ·cell −1 . The seedlings were cultivated in the green coir dust substrate with wormcompost (3:1) and they were irrigated with a 3 mm water level twice a day. At 52 and 83 days after the transplant, number of leaves, largest width of the 3rd leaf and largest diameter of the r osette were evaluated. Between 93 and 97 days, root and shoot fresh/dry weight were analyzed . The experimental design was a randomized block with 4 treatments and 5 repetition s for the variables related to foliar development, and with 4 treatments and 4 repetition s for the variables related to plant weight. Results evidenced the best development of the micro propagated ornamental pineapple seedlings when: were irrigated with a 1 mm water level at 52 DAT and with a 2 mm at 83 DAT; were irrigated twice a day during whole experiment; were cultivated in 180 cm 3 plastic containers and when the substrate used was composed by dry coir dust and wormcompost.